When Games Turn Into Debt: Legal Analysis of Online Game Transactions - Palu, Selvia; Arief, Anggreany; Aswari, Aan (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to determine and analyze the fulfillment of the application of proficiency requirements by payment service providers when purchasing online game items. To find out and analyze the efforts that online game service users can take to deal with the losses they experience. The research method used is the Normative research method, namely a legal research method that is sourced from regulatory and secondary document data in the form of collection from library and tertiary materials which are documents that contain concepts and information such as dictionaries. The results of this research show that the sale and purchase agreement for payment services for buyers of online game items does not fulfill the subjective and objective requirements which are the legal requirements for an agreement. The condition that is not fulfilled is that those who bind themselves agree to a certain thing and a lawful cause. for consumers for losses received due to irresponsibility of business actors in paying off transactions is clearly regulated in article 19 UUPK. However, if the business actor's number can be contacted, the perpetrator can be held responsible for compensation. Recommendations for this research: The government should also have more awareness and supervision of legal issues that arise in society, so that it can quickly act against negative elements that endanger society.